Evaluation of round fruited brinjal genotypes for yield, quality and tolerance to fruit and shoot borer. - Kranthi Rekha Gogula (Department of Olericulture, College of Agriculture, 2011)
The present investigation on “Evaluation of round fruited brinjal genotypes for yield, quality and tolerance to fruit and shoot borer” was conducted at the Department of Olericulture, College of Agriculture, Vellayani, during the period 2010-2011. The objective of the study was to assess the genetic variability for yield, quality and resistance to fruit and shoot borer and elucidating the morphological, anatomical and biochemical basis of fruit and shoot borer resistance. The study was conducted in two separate experiments. 1. Screening brinjal genotypes for yield and fruit and shoot borer resistance 2. Evaluation of genotypes for genetic variability, yield, quality and tolerance to pests and diseases. In experiment I, thirty four accessions of brinjal were collected from different parts of country and grown in the field in RBD with three replications. Analysis of variance revealed that significant difference among the accessions for all the characters studied. SM 49 and SM 36 showed lowest infestation to fruit and shoot borer while SM 23 showed highest. Among other pests, SM 36 and SM 40 had severe incidence of jassids and ash weevils respectively. In experiment II, the yield ranged from 3.62 kg to 0.66 kg. SM 49 was superior for plant height, percentage of long and medium styled flowers and yield. Highest fruit weight was in SM 44. High phenotypic coefficient of variation and genotypic coefficient of variation were observed for yield per plant, fruits per plant, fruit weight and branches per plant. High heritability and high genetic advance also observed for these characters. At genotypic level, yield per plant had high positive correlation with percentage of long and medium styled flowers, branches per plant, fruit length and plant height. The path analysis showed that percentage of long and medium styled flowers, branches per plant, fruit length and fruits per plant had direct effect on yield per plant. SM 49 followed by SM 44, SM 23, SM 41 and SM 30 was having the highest selection index values based on discriminant function analysis. Based on Mahalanobis D2 analysis the current genotypes were grouped into five clusters. Cluster I being the largest including with twenty accessions and cluster II and V had one each. Cluster V had highest values for seven characters viz., plant height, secondary branches, percentage of long and medium styled flowers, fruit length, fruits per plant and yield per plant. Highest inter cluster distance was between cluster II and V. Maximum intra cluster distance was in cluster IV. In screening for fruit and shoot borer resistance, the incidence ranged from 4.77 to 31.97 per cent and 10.83 to 63.01 per cent for shoot and fruit respectively. However accessions viz., SM49 and two local collections SM 44 and SM 36 showed moderate resistance to fruit and shoot borer. Fruit colour was related to fruit and shoot borer tolerance. Light coloured fruits were less susceptible. More RLPS and less RLSA led to tolerance. In moderately resistant accessions there was more number and well developed vascular bundles compare to susceptible ones. High phenol and proline content and less sugars and protein content were responsible for resistance to fruit and shoot borer incidence. Accession like SM 23, SM 36, SM 40, SM 44, SM 45 and SM 49 showed high level of resistance to bacterial wilt. The accessions SM 36, SM 44, SM 45 and SM 49 showed resistance to both fruit and shoot borer and bacterial wilt. The study identified the high yielding, large fruited SM 44 with resistance to fruit and shoot borer and bacterial wilt as a promising line for cultivation in Kerala after further confirmatory studies.